2021
DOI: 10.17576/jsm-2021-5006-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indoor Air Quality in Relation to Ventilation Practices in Hospitals of Lahore, Pakistan

Abstract: Temporal variations of particulate matter (PM) and carbon dioxide (CO2 ) in orthopedic wards and emergency rooms of different hospitals of Lahore, Pakistan were investigated. Hospitals were classified into two groups, I (centrally air-conditioned) and II (non-central air-conditioned) based on the ventilation system. Statistical analysis indicated significantly lower PM and CO2 levels in centrally air-conditioned hospitals in comparison to non-central air-conditioned. The low indoor-outdoor (I/O) ratio of PM2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
9
1
1
Order By: Relevance
“…In this way, there are 8 groups of articles: hospital ward, isolation room, Intensive Care Unit (ICU) room, various, operation room, emergency department, Biocontainment Unit (BCU), and alternative care sites, according to Table 4 . It is noteworthy that, in the case of the classification “various”, there are articles that address the entire floor of a hospital [ 18 ], which carried out a literature review article related to the subject [ 30 ], and that address more than one environment classification [ 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, there are 8 groups of articles: hospital ward, isolation room, Intensive Care Unit (ICU) room, various, operation room, emergency department, Biocontainment Unit (BCU), and alternative care sites, according to Table 4 . It is noteworthy that, in the case of the classification “various”, there are articles that address the entire floor of a hospital [ 18 ], which carried out a literature review article related to the subject [ 30 ], and that address more than one environment classification [ 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, in the case of the classification “various”, there are articles that address the entire floor of a hospital [ 18 ], which carried out a literature review article related to the subject [ 30 ], and that address more than one environment classification [ 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a case study in Bangkok regarding the relationship between indoor and outdoor PM2.5 concentrations in different conditions (open and closed ventilation systems) reported the PM2.5 concentrations in the closed ventilation area in each place in terms of Indoor/Ambient ratio (I/A ratio) ranged from 0.37 to 3.57, indicating that outdoor PM2.5 can enter the buildings through the ventilation system and infiltration (Sompornrattanaphan et al, 2018). Similarly, indoor PM2.5 concentrations in non- central air-conditioned hospitals were reported to be associated with outdoor concentrations indicating the impact of ambient air quality in urban centers on IAQ (Nimra et al, 2021). Lee et al (2020) studied the intervention effect on IAQ in hospitals and found that only PM2.5 concentrations decreased in rooms employing an air-cleaner.…”
Section: Comparison Of Iaq In the Sampling Areas With Different Venti...mentioning
confidence: 98%